Pengembangan Multimedia Gamifikasi Kolaboratif untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran Sistem Komputer - Pradnyana, I Ketut Andika; Mertayasa, I Nengah Eka; Subawa, I Gede Bendesa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2025)
This study aims to develop and implement collaborative gamification-based multimedia to enhance students’ critical thinking skills in the Computer Systems course. The background of the study highlights the need to strengthen students’ critical thinking, particularly when engaging with complex content such as Computer Systems. Teacher-centered instruction and limited student interaction can hinder the development of critical thinking skills. Therefore, this research seeks to address these issues by applying a collaborative learning model that leverages gamification principles. The research employs a research and development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model. The stages include analyzing learner characteristics, designing the multimedia, collecting materials, and assembling the multimedia. Data analysis utilizes Gregory’s formula to assess the validity of the collaborative gamified multimedia. The expected output is the development of collaborative gamified multimedia that effectively improves students’ critical thinking skills in the Computer Systems course. This multimedia is anticipated to serve as an engaging and interactive learning resource that fosters student involvement in the learning process. Overall, the study is expected to contribute to the advancement of innovative instructional models that enhance students’ critical thinking skills in Computer Systems.